2014
DOI: 10.1179/2295333714y.0000000050
|View full text |Cite
|
Sign up to set email alerts
|

Patient-reported frequency, awareness and patient-physician communication of hypoglycaemia in Belgium

Abstract: Hypoglycaemic events and unawareness of these events are common in Belgian insulin-treated diabetes patients. Patients often fail to report hypoglycaemic events to their physician and many physicians do not inquire about hypoglycaemia, meaning the current burden of hypoglycaemic events may be underestimated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 23 publications
2
14
1
1
Order By: Relevance
“…A minority of patients in our study reported awareness of hypoglycemia (5.9%); the majority however reported either impaired awareness (83.4%) or unawareness (10.7%). Similar findings were found in previous studies in different countries ranging from 43% to 75% (Gehlaut et al, 2015; Kulzer, Seitz & Kern, 2014; Peene et al, 2014; Östenson et al, 2014). In our study, people who reported impaired awareness of hypoglycemia were higher.…”
Section: Discussionsupporting
confidence: 92%
“…A minority of patients in our study reported awareness of hypoglycemia (5.9%); the majority however reported either impaired awareness (83.4%) or unawareness (10.7%). Similar findings were found in previous studies in different countries ranging from 43% to 75% (Gehlaut et al, 2015; Kulzer, Seitz & Kern, 2014; Peene et al, 2014; Östenson et al, 2014). In our study, people who reported impaired awareness of hypoglycemia were higher.…”
Section: Discussionsupporting
confidence: 92%
“…This compares with an overall crude rate of 1.4 ± 2.1 events ( n =37) in the present study over the same period, despite a greater proportion of insulin and sulfonylurea users at baseline (56%), with only two participants not on hypoglycaemic medication. This rate is substantially lower compared with recently published rates of hypoglycaemia in comparable populations . This is probably explained by the combination of hypoglycaemic education, a proactive reduction in hypoglycaemic medication, and weekly contact to discuss hypoglycaemia.…”
Section: Discussioncontrasting
confidence: 63%
“…Our primary outcome was reliant on self‐reported hypoglycaemia during weekly contact. While spontaneously self‐reported hypoglycaemia rates are low in people with Type 2 diabetes , self‐reported hypoglycaemia in response to questionnaires is a widely used measure of the true burden of hypoglycaemia in population studies . In retrospect, it would have been helpful to have collected data on rates of hypoglycaemia prior to the commencement of the intervention.…”
Section: Discussionmentioning
confidence: 99%
“…Recent evidence from Taiwan and Korea shows a worrying sharp rise in emergency admissions for hypoglycaemia in older patients, which further emphasizes the importance of our meta-analysis [24,25]. In addition, studies that used rigorous methods for ascertaining hypoglycaemia have found that the burden of hypoglycaemic events may be higher than envisaged [26,27] A number of mechanistic reasons have been identified to explain why hypoglycaemic events can lead to cognitive impairment (e.g. neuroglycopaenia).…”
Section: Discussionmentioning
confidence: 98%